Students' perceptions of the use quizizz as an online learning media for biology - Qurrota Aýun; Irsyad Purbha Irwansyah (Biosfer: Jurnal Pendidikan Biologi, 2022)
During this covid-19 pandemic, Quizizz, as an Android-based educational game application, can be used to encourage students to be active and motivated in distance learning. This study aims to determine students' perceptions of the use of quizizz in motivating the students to study biology during online learning. The study population was all students of class IX MTs As-Saádah. The total number of respondents was 48 students. Data analysis was performed using the quantitative descriptive percentage technique. The research data was obtained by distributing questionnaires using the google form application. The questionnaire showed that 79.2% and 54.2% of students' perceptions regarding using the most preferred and good learning media were Quizizz. 45.8% of students showed interest in taking biology lessons using quizizz. 62.5% and 47.9% of students are motivated and enthusiastic about getting high scores. 89.6% and 66.7% of students agree that quizizz can improve their learning outcomes and concentration. 66.7% of students answered that the level of difficulty of quizizz questions was moderate, and 64.5% of students chose to agree that quizzz provided a new learning experience. The use of quizizz in online biology learning is a media recommendation that is appropriate, interesting and fun for students.